Symmetries and conservation laws for the Karczewska–Rozmej–Rutkowski–Infeld equation. (December 2016) - Sergyeyev, A.; Vitolo, R.
Abstract: We give a complete description of generalized symmetries and local conservation laws for the fifth-order Karczewska–Rozmej–Rutkowski–Infeld equation for shallow water waves in a channel with variable depth. In particular, we show that this equation has no genuinely generalized symmetries and thus is not symmetry integrable.